A Systematic Review and International Web-Based Survey of Randomized Controlled Trials in the Perioperative and Critical Care Setting: Interventions Reducing Mortality - Sartini, Chiara; Lomivorotov, Vladimir; Pieri, Marina; Lopez-Delgado, Juan Carlos; Baiardo Redaelli, Martina; Hajjar, Ludhmila; Pisano, Antonio; Likhvantsev, Valery; Fominskiy, Evgeny; Bradic, Nikola; Cabrini, Luca; Novikov, Maxim; et al. (Elsevier, 2019)
The authors aimed to identify interventions documented by randomized controlled trials (RCTs) that reduce mortality in adult critically ill and perioperative patients, followed by a survey of clinicians’ opinions and routine practices to understand the clinicians’ response to such evidence. The authors performed a comprehensive literature review to identify all topics reported to reduce mortality in perioperative and critical care settings according to at least 2 RCTs or to a multicenter RCT or to a single-center RCT plus guidelines. The authors generated position statements that were voted on online by physicians worldwide for agreement, use, and willingness to include in international guidelines. From 262 RCT manuscripts reporting mortality differences in the perioperative and critically ill settings, the authors selected 27 drugs, techniques, and strategies (66 RCTs, most frequently published by the New England Journal of Medicine [13 papers], Lancet [7], and Journal of the American Medical Association [5]) with an agreement ≥67% from over 250 physicians (46 countries). Noninvasive ventilation was the intervention supported by the largest number of RCTs (n = 13). The concordance between agreement and use (a positive answer both to “do you agree” and “do you use”) showed differences between Western and other countries and between anesthesiologists and intensive care unit physicians. The authors identified 27 clinical interventions with randomized evidence of survival benefit and strong clinician support in support of their potential life-saving properties in perioperative and critically ill patients with noninvasive ventilation having the highest level of support. However, clinician views appear affected by specialty and geographical location. © 2018 Elsevier Inc.